Derivative backoff: The other saturation problem for PID controllers. (September 2015) - Theorin, Alfred; Hägglund, Tore
Abstract : Highlights: A new issue with the derivative part for PID controller has been discovered. The issue has been analyzed and explained in detail. Various ways to address the issue are discussed. A solution to the issue is presented and evaluated. A simple patch for existing PID implementations is provided. Abstract: The PID controller is by far the most common controller, and to ensure good behavior under all circumstances, a PID implementation must consider many practical aspects such as integrator windup, derivative kick, and bumpless parameter and mode changes. In this paper, an entirely new issue for the derivative part is introduced and has been named derivative backoff. It occurs when the process value measurement saturates and is a general issue that affects all PID implementations. Derivative backoff is described in detail and it is shown that it can cause considerable, undesired, effects on industrially relevant processes even when they are controlled by well-tuned PID controllers. An anti-backoff strategy for PID controllers with integral action is proposed and evaluated, and a simple patch for existing PID implementations is presented. Possible strategies for PID controllers without integral action are also discussed.